Comparison of Postoperative Condylar Functions of Orthognathic Surgery Patients with Control Subjects Using SAM Axiograph - Barış Ünlü; Berza Şen; Nazan Küçükkeleş; Nejat Erverdi (Galenos Yayinevi, 2011)
Aim:The aim of this study is to compare temporomandibular joint tracings of healthy individuals, who do not manifest any TMD symptoms, with those of the patients who have undergone orthognathic surgery operations after a certain period of time.Subjects and Methods:Fifty adults who have undergone orthognathic surgery operations have been divided into subgroups in accordance with the type of surgery plan and they were compared with the control group without any TMJD, as well as with the other surgery subgroups. SPSS packed programe's Student's t test were used for the statistical analysis.Results:Significant tracing widening and shortening was observed in the advancement surgery and setback surgery groups compared to the control group. Especially the postoperative data of mandibular advancement cases showed reduced mobility and more discrepancy in width compared to the control group and mandibular setback group.Conclusion:Patients, who have undergone advancement surgery, have to be analyzed carefully since these patients are more prone to develop TMDS. None of the patients among mandibular advancement surgery group in our study needed help for their current status. This study shows that after orthognathic surgery, lower jaw movements are more limited and less reproducible, and these results are even more severe in mandibular advancement surgery cases.